2020
DOI: 10.21203/rs.3.rs-100810/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered Tyrosine Phosphorylation of Cardiac Proteins Prompts Contractile Dysfunction in Hypertrophic Cardiomyopathy

Abstract: Altered Serine/Threonine phosphorylation of the cardiac proteome is an established hallmark of heart failure (HF). However, the contribution of tyrosine phosphorylation to the pathogenesis of these diseases remains unclear. The cardiac proteome was explored by global mapping to discover and quantify site-specific tyrosine phosphorylation in two cardiac hypertrophic models; cardiac overexpression of ErbB2 (TgErbB2) and cardiac expression of α-Myosin heavy chain R403Q (R403Q-αMyHCTg) compared to control hearts. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Regarding the main signaling modules, Davis et al 11 indicated the myofilament force-generation module, CaN-NFAT, and ERK1/2 pathways regulate mass and eccentricity in familial cardiomyopathy. In addition, other signaling pathways such as PI3K-AKT 14,21 , NO-PKG 15,26 , calcium 27 , β-adrenergic 13,28 , and downstream pathways of Gq protein 29 and growth factor receptors 30,31 could play a role in familial cardiomyopathy. Moreover, titin has been described as a regulator of familial cardiomyopathy via its effects on cardiomyocyte stiffness, force generation 32 , and mechanotransduction 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the main signaling modules, Davis et al 11 indicated the myofilament force-generation module, CaN-NFAT, and ERK1/2 pathways regulate mass and eccentricity in familial cardiomyopathy. In addition, other signaling pathways such as PI3K-AKT 14,21 , NO-PKG 15,26 , calcium 27 , β-adrenergic 13,28 , and downstream pathways of Gq protein 29 and growth factor receptors 30,31 could play a role in familial cardiomyopathy. Moreover, titin has been described as a regulator of familial cardiomyopathy via its effects on cardiomyocyte stiffness, force generation 32 , and mechanotransduction 33 .…”
Section: Resultsmentioning
confidence: 99%
“…We also found the DEGs between two clusters were mainly involved in cell adhesion molecules cams, Ecm receptor interaction, focal adhesion, oxidative phosphorylation, regulation of actin cytoskeleton and tight junction. Previous studies have reported the altered tyrosine phosphorylation may play a regulatory role in cardiac hypertrophic models [23]. Tyrosine/serine phosphorylated focal adhesion kinase are required for the hypertrophic response of cardiomyocytes to growth factors and mechanical load that may explained the machanism of cell spreading and sarcomere reorganization in HCM [24].…”
Section: Discussionmentioning
confidence: 96%
“…Williams syndrome (WS) is a rare inherited multi-system disease which caused by < 2-megabase pair (Mb) deletion of chromosome 7q11. 23. It occurs in as many as 1:7500-25000 individuals [6].…”
Section: Introductionmentioning
confidence: 99%